A novel bulk eutectic high-entropy alloy with outstanding as-cast specific yield strengths at elevated temperatures. (November 2021) - Wang, Mingliang; Lu, Yiping; Wang, Tongmin; Zhang, Chuan; Cao, Zhiqiang; Li, Tingju; Liaw, Peter K.
Abstract: Due to their excellent properties and great potential for industrial application, eutectic high-entropy alloys (EHEAs) have been a hot topic of study over the past few years. The current study reports a novel AlCr1.3 TiNi2 EHEA with a low density and outstanding mechanical properties at elevated temperatures. A kilogram-scale EHEA ingot with uniform and ultrafine L21 and BCC lamellar structures (interlamellar spacing ~ 400 nm) was firstly prepared by a direct solidification method. The as-cast AlCr1.3 TiNi2 EHEA exhibits much higher room- and high-temperature hardness and specific yield strength values than most reported refractory high-entropy alloys (RHEAs), EHEAs, and conventional Ni- and Ti-based alloys. Graphical abstract: Image, graphical abstract